THE CHALLENGES OF JAKARTA’S DEVELOPMENT AND MANAGEMENT AND PROSPECTS OF DRONE TECHNOLOGY UTILIZATION - Lestari, Nadia Ayu Rahma; Fahmi, Erwin; Sulistia, Erlando; Kim, Doo Pyo; Kwak, Jae Ha (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2024)
The development and management of Jakarta confront numerous obstacles, including inadequate infrastructure, increasing weather extremity, population growth, and shifts in residential, occupational, and shopping habits. Attempts to tackle these difficulties are often restricted by financial, institutional, and technological constraints. The ongoing improvement of drone technology provides real-time and cost-effective data collecting for inspection, monitoring, and addressing daily challenges in urban management. This paper used a straightforward case study on Panggang Island, located offshore from Jakarta, to explore the prospect of drone technology in addressing the challenges faced by Jakarta. The study employs a qualitative methodology, combining desk study, literature review, and a case study approach. The findings indicate that the prospects for this application are evident and robust.